Artificial Intelligence for Predictive Risk Management in Islamic Banking: Opportunities and Ethical Challenges - Aisyah Defy Rahmayani Simatupang; Yui Nakamura; Sakura Suzuki (Yayasan Adra Karima Hubbi, 2025)
The integration of Artificial Intelligence (AI) into Islamic banking introduces transformative possibilities for predictive risk management while simultaneously raising crucial ethical concerns. This study explores how AI-driven analytics can enhance the accuracy of risk prediction, compliance efficiency, and Sharia-based decision-making processes in Islamic financial institutions. The purpose of this research is to analyze both the technological opportunities and the ethical challenges that accompany AI applications in Islamic banking risk management. Using a qualitative descriptive approach supported by literature analysis and expert interviews, the study investigates AI’s role in mitigating financing risks, improving operational transparency, and ensuring adherence to maqasid al-shariah principles. The findings reveal that AI facilitates efficient monitoring of risk indicators and supports data-driven decisions aligned with Islamic ethics. However, ethical issues such as algorithmic bias, data privacy, and the loss of human judgment remain significant concerns. The study concludes that successful AI adoption in Islamic banking requires a balanced framework integrating technological advancement with ethical governance rooted in Islamic moral values.